The materiality of literary narratives in urban history
1 online resource.
Keywords: "The Materiality of Literary Narratives in Urban History explores a variety of geographical and cultural contexts to examine what literary texts, grasped as material objects and as reflections on urban materialities, have to offer for urban history. The contributing writers' approach to literary narratives and materialities in urban history is summarized within the conceptualization 'materiality in/of literature': the way in which literary narratives at once refer to the material world and also actively partake in the material construction of the world. This book takes a geographically multipolar and multidisciplinary approach to discuss cities in the UK, USA, India, South Africa, Finland, and France, whilst examining a wide range of textual genres from the novel to cartoons, advertising copy, architecture and urban planning, and archaeological writing. In the process, attention is drawn to narrative complexities embedded within literary fiction and to the dialogue between narratives and historical change. The Materiality of Literary Narratives in Urban History has three areas of focus: literary fiction as form of urban materiality, literary narratives as social investigations of the material city, and the narrating of silenced material lives as witnessed in various narrative sources"--